EFFECTIVENESS OF AL-MIFTAH LIL ULUM METHOD IN IMPROVING UNDERSTANDING OF NAHWU MTS TANWIRUL QULUB LAMONGAN - Evy Nur Rohmawaty; Munirul Abidin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
Teaching methods are crucial in the process of learning Nahwu . The Nahwu teaching method applied at MTs Tanwirul Qulub Lamongan still uses conventional methods, which lead to learning problems among students. The students struggle to understand Nahwu material properly, face difficulties in memorizing the material, and have trouble creating examples of rule application. Based on these issues, there is a need for an appropriate teaching method to address these problems effectively. This study uses a quantitative method and employs a quasiexperimental design to determine the effectiveness of the Al-Miftah Lil Ulum method in improving the nahwu understanding of eighth-grade students. The subjects of this study were 60 eighth-grade students from MTs Tanwirul Qulub, consisting of 30 students from class A and 30 students from class B. Tests, observation sheets, and documentation sheets were used to collect data. The research utilized a comparative descriptive method and t-test to analyze the data. The findings showed that the t-test value at the t-count value was 3.289, which is greater than the ttable value, and the sig. (2-tailed) value was 0.000, which is less than 0.05. This was then used to test the hypothesis. The results indicated that Ho was rejected and Ha was accepted, meaning that the application of the Al-Miftah Lil Ulum method is effective in improving nahwu understanding compared to conventional methods among eighth-grade students at MTs Tanwirul Qulub Lamongan.